A educação superior a distância: políticas e dinâmicas da formação de professores em Ead em Santa Catarina - Toledo, Jaques Antonio de (2020)
The thesis presents the results of a research about Higher Distance Education (DE) in Brazil and in the State of Santa Catarina between 1998 and 2018. The study aimed to comprehend the main factors that directly impacted the expansion of this teaching modality. More specifically, it analyzes (i) the main regulatory goals of Distance Education and the expansion and evaluation policies implemented in the period; (ii) the dynamics and characteristics of the expansion according to the administrative nature, academic degree and professional area; (iii) the role of distance education in the field of teacher training. It was decided to concentrate the study on a specific state of the federation, the State of Santa Catarina. The research was developed through an extensive bibliographic and documentary research, and the survey and analysis of data about formal higher education and higher distance education available by INEP/MEC. The first part of the research focused on the analysis of DE regulatory goals in Brazil. Then, the quantitative data available in the INEP database were systematized. This data was available by the agency to the researcher through the microdata of higher education. The data were organized into numerous categories of analysis. The data show the growth of education institutions, courses and distance education enrollments in the period. While face-to-face undergraduate enrollments grew 43.5% between 2005 and 2018, distance education grew by 1,693%, from 114,642 in 2005 to 2,056,511 in 2018. According to INEP data, in 2005 there were 189 distance undergraduate courses in Brazil. In 2018, that number increased to 3,177, which is a growth corresponding to 1,560%. In 2018, one in four higher education students was enrolled in distance education. The Higher Education Census of 2018 recorded that face-to-face enrollments fell by about 2% between 2017 and 2018. Meanwhile, the number of enrollments for distance education increased by 17%, from 1,756,982 in 2017 to 2,056,511 in 2018. Regarding to undergraduate courses, the 2018 Higher Education Census also revealed the number of students enrolled in distance education courses were higher than the number of students enrolled in face-to-face courses (50.2% in distance education against 49.8% face-to-face).